Our tenth anniversary (Humanities & Social Sciences Communications)
This journal launched in January 2015 with a mission to publish robust scholarship from across and between all areas of the humanities, and social and behavioural sciences. Here, we look back at how we have stayed true to our guiding mission and reflect on what lies ahead for this journal but also scholarly publishing more broadly.